Targeted mutation of the outer membrane protein P66 disrupts attachment of the Lyme disease agent, Borrelia burgdorferi, to integrin α(v)β(3) - Coburn, Jenifer (National Academy of Sciences, 2003)
Borrelia burgdorferi, the agent of Lyme disease, expresses several adhesion molecules that are probably required for initial establishment of infection in mammalian hosts, and for colonization of various tissues within the host. The B. burgdorferi outer membrane protein P66 was previously identified as a ligand for β(3)-chain integrins by using a variety of biochemical approaches. Although the earlier data suggested that P66 is an adhesin that mediates B. burgdorferi attachment to β(3)-chain integrins, lack of genetic systems in B. burgdorferi precluded definitive demonstration of a role for P66 in β(3) integrin attachment by intact borreliae. Recent advances in the genetic manipulation of B. burgdorferi have now made possible the targeted disruption of the p66 gene. Mutants in p66 show dramatically reduced attachment to integrin α(v)β(3). This is, to our knowledge, the first description of the targeted disruption of a candidate B. burgdorferi virulence factor with a known biochemical function that can be quantified, and demonstrates the importance of B. burgdorferi P66 in the attachment of this pathogenic spirochete to a human cell-surface receptor.